Looking for natural hydrogen in Albania and Kosova - Lévy, Dan; Boka-Mene, Molly; Meshi, Avni; Fejza, Islam; Guermont, Thomas; Hauville, Benoît; Pelissier, Nicolas (Frontiers in Earth Science, 2023)
A regional geochemistry field study was conducted in Albania and Kosova to spot natural H2 occurrences related to ophiolitic massifs. 21 sites, mainly consisting in natural springs, were studied and 9 were sampled for analyzing associated free gas and C, H isotopes of CH4 and H2 when possible. Four springs exhibited gas with H2 occurrence, one particularly reaching 16% of H2 in the North of Kosova in a location named Vuçe, which makes it the fifth gas seep the most enriched in H2 in the Dinarides, after H2-rich gas seeps in Serbia and Bosnia and Herzegovina. This gas seep is associated with hyperalkaline water having a pH of about 10.7. This would favor that H2 derives from the serpentinization of peridotites, process which is likely still ongoing. The H2 is associated with mainly N2 and CH4, like the other H2-rich gas springs in the Dinarides. Based on C and H isotopes, the CH4 is abiotic or microbial. H isotopes suggest a formation of H2 at about 2 km deep. One other hyperalkaline spring was found in the South of Albania, at the border of the Korça Basin, with less than 200 ppm of H2. No relation between H2 and He was identified at the scale of Albania and Kosova, nor at the scale of the whole Dinarides. This work provides completed map of the H2 occurrences in the Dinarides and allows to highlight some hot spots for H2 exploration, located mainly inside the ophiolitic massifs like in other ophiolites (such as Oman, New Caledonia and Philippines), and not on major faults like in the Pyrenees.